Microfabricated electrochemical sensing devices. Issue 8 (4th March 2020) - Sassa, Fumihiro; Biswas, Gokul Chandra; Suzuki, Hiroaki
Abstract : Electrochemistry provides possibilities to realize smart microdevices of the next generation with high functionalities. Abstract : Electrochemistry provides possibilities to realize smart microdevices of the next generation with high functionalities. Electrodes, which constitute major components of electrochemical devices, can be formed by various microfabrication techniques, and integration of the same (or different) components for that purpose is not difficult. Merging this technique with microfluidics can further expand the areas of application of the resultant devices. To augment the development of next generation devices, it will be beneficial to review recent technological trends in this field and clarify the directions required for moving forward. Even when limiting the discussion to electrochemical microdevices, a variety of useful techniques should be considered. Therefore, in this review, we attempted to provide an overview of all relevant techniques in this context in the hope that it can provide useful comprehensive information.